2017
DOI: 10.1038/s41536-017-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical imaging methods for assessing the safety and efficacy of regenerative medicine therapies

Abstract: Regenerative medicine therapies hold enormous potential for a variety of currently incurable conditions with high unmet clinical need. Most progress in this field to date has been achieved with cell-based regenerative medicine therapies, with over a thousand clinical trials performed up to 2015. However, lack of adequate safety and efficacy data is currently limiting wider uptake of these therapies. To facilitate clinical translation, non-invasive in vivo imaging technologies that enable careful evaluation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
89
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 123 publications
(131 reference statements)
0
89
0
1
Order By: Relevance
“…After production, radiotracers are unstable, immediately lose their energy and generate some particles named as positrons. These particles interact with neighbouring electrons via annihilation process, and two produced photons (each having 511 keV energy) can be detected by PET scanners . Cell labelling PET radiotracers include 2‐[F‐18]‐fluoro‐2‐deoxy‐D‐glucose ( 18 F‐FDG) and [ 64 Cu]‐pyruvaldehyde‐bis (N4‐methylthiosemicarbazone) ( 64 Cu‐PTSM).…”
Section: Molecular Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…After production, radiotracers are unstable, immediately lose their energy and generate some particles named as positrons. These particles interact with neighbouring electrons via annihilation process, and two produced photons (each having 511 keV energy) can be detected by PET scanners . Cell labelling PET radiotracers include 2‐[F‐18]‐fluoro‐2‐deoxy‐D‐glucose ( 18 F‐FDG) and [ 64 Cu]‐pyruvaldehyde‐bis (N4‐methylthiosemicarbazone) ( 64 Cu‐PTSM).…”
Section: Molecular Imagingmentioning
confidence: 99%
“…Cell labelling PET radiotracers include 2‐[F‐18]‐fluoro‐2‐deoxy‐D‐glucose ( 18 F‐FDG) and [ 64 Cu]‐pyruvaldehyde‐bis (N4‐methylthiosemicarbazone) ( 64 Cu‐PTSM). Single‐photon emission computed tomography (SPECT) imaging relies on detection of two low‐energy γ (gamma) photons being emitted from radioisotopes including 111 In‐oxine and technetium ( 99m Tc) exametazime ( 99m Tc‐hexamethyl propylene amine oxime [HMPAO]) …”
Section: Molecular Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a highly sensitive and robust method of monitoring the biodistribution of cells though it has a low spatial resolution (intra and inter organ monitoring of cells distribution is not possible). 15 . CC-BY-NC-ND 4.0 International license It is made available under a was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
“…34 We and others have shown that most cells die after injection. 11,15,35 Therefore, understanding the in vivo fate of cell-labelling nanoparticles, especially following the death of the labelled cells is important for the interpretation of imaging studies and to assess the risk of toxicity. In the current study, we focus on the effect of formulation on the fate of SPIONs after the in vivo injection of labelled cells.…”
Section: Introductionmentioning
confidence: 99%